2023
DOI: 10.3390/metabo13050648
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantitation and Discovery (SQUAD) Analysis: Combining the Best of Targeted and Untargeted Mass Spectrometry-Based Metabolomics

Abstract: Untargeted and targeted approaches are the traditional metabolomics workflows acquired for a wider understanding of the metabolome under focus. Both approaches have their strengths and weaknesses. The untargeted, for example, is maximizing the detection and accurate identification of thousands of metabolites, while the targeted is maximizing the linear dynamic range and quantification sensitivity. These workflows, however, are acquired separately, so researchers compromise either a low-accuracy overview of tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Jia and colleagues (2019) integrated targeted and non-targeted methods for exposomics of human urine by isotopically tagging exposure biomarkers with common functional groups (e.g., phenolic, hydroxyl, carboxyl, and primary amine) that can simultaneously be leveraged for quantitative purposes . Likewise, the single-injection s imultaneous q uantitation a nd d iscovery (SQUAD) approach, developed for metabolomics, identifies (via ASDs) and quantifies (via calibration curves or one-point calibration using ASDs and ISDs) select compounds while allowing simultaneous data mining to look for broader molecular changes . Second, the feasibility would largely depend on the specific instrumental capacity in use.…”
Section: Toward Merging Targeted and Non-targeted Approachesmentioning
confidence: 99%
“…Jia and colleagues (2019) integrated targeted and non-targeted methods for exposomics of human urine by isotopically tagging exposure biomarkers with common functional groups (e.g., phenolic, hydroxyl, carboxyl, and primary amine) that can simultaneously be leveraged for quantitative purposes . Likewise, the single-injection s imultaneous q uantitation a nd d iscovery (SQUAD) approach, developed for metabolomics, identifies (via ASDs) and quantifies (via calibration curves or one-point calibration using ASDs and ISDs) select compounds while allowing simultaneous data mining to look for broader molecular changes . Second, the feasibility would largely depend on the specific instrumental capacity in use.…”
Section: Toward Merging Targeted and Non-targeted Approachesmentioning
confidence: 99%
“…20,21 Specifically, targeted metabolomics is the validation and analysis of specific metabolites, while untargeted metabolomics is a comprehensive and systematic analysis of the organism's metabolites. 22 In this study, we isolated a new Streptomyces strain SN40 whose fermentation filtrate can effectively suppress the infection of TMV and PVY in plants. Physiological, biochemical classification and phylogenetic analysis showed that the Streptomyces strain SN40 is most closely related to Streptomyces albulus.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has been widely used in the fields of agriculture, medicine, pharmacy, and food chemistry, which is generally based on nuclear magnetic resonance (NMR), and gas chromatography (GC) or liquid chromatography (LC) coupled to mass spectrometry (MS) analytical techniques. , Specifically, targeted metabolomics is the validation and analysis of specific metabolites, while untargeted metabolomics is a comprehensive and systematic analysis of the organism’s metabolites …”
Section: Introductionmentioning
confidence: 99%
“…As future directions, the authors highlight the efforts needed towards the combination of targeted and untargeted metabolomics approaches via untargeted MS1 data acquisition and high-resolution MRM transitions for targeting multiple metabolites. More recently, Bird et al (2023) 10 have introduced a new workflow based on orbitrap and/or TOF systems (SQUAD, Simultaneous Quantitation and Discovery Analysis) aiming at combining both targeted and untargeted with the main objective of finding the equilibrium between untargeted and targeted approaches in a single experiment. This paper describes, to the best of our knowledge, the first targeted/untargeted, single-injection LC-MS method for integrated exposomics and metabolomics, combining the advantages of both approaches, i.e., ultrahigh sensitivity (targeted) and broad coverage and retrospective data analysis (untargeted).…”
Section: Introductionmentioning
confidence: 99%